Effectiveness of different selection indices for genetic improvement in Murrah buffaloes - KURALKAR, S V; RAHEJA, K L (The Indian Journal of Animal Sciences, 2013)
Eleven selection indices incorporating first lactation traits, viz. age at first calving, first lactation milk yield, first lactation length and tirst calving interval of buffaloes, were constructed and compared. Results indicated that selection based on an index containing first lactation milk yield and first lactating length was best which will bring maximum simultaneous genetic gain in these traits and as well as in total aggregate genetic merit.